Evaluating Evidence of Mechanisms in Medicine : Principles and Procedures /: Principles and Procedures. (2018) - Parkkinen, Veli-Pekka; Wallmann, Christian; Wilde, Michael; Clarke, Brendan; Illari, Phyllis; Kelly, Michael P; Norell, Charles; Russo, Federica; Shaw, Beth; Williamson, Jon
No abstract available